Estimation of Near-Surface Soil Density Using Electrical and Electromagnetic Geophysical Techniques - Franko, Kelsey M. (My University, 2014)
Soil density is an important parameter for a variety of applications in agriculture, geology, and geotechnical engineering. Conventional methods for measuring soil density are expensive, time-consuming, and destructive, so soil density is often not adequately characterized. In contrast, near-surface geophysical methods are largely noninvasive, allow temporal monitoring, and are often useful for mapping large areas, so they offer significant advantages over conventional techniques for estimating soil density. This experiment explores the potential of five geophysical techniques: ground penetrating radar (GPR), time domain reflectometry (TDR), low-frequency electromagnetics, electrical resistivity, and magnetic induction for estimating soil density.
Color poster with text, graphs, and images.
Keywords: Magnetic induction; Electrical resistivity; Low-frequency electromagnetics; Time domain reflectrometry (TDR); Ground penetrating radar; Soil density; Posters